Effectiveness of Ayurvedic Treatments in Shiwtra of Children w.s.r. of Vitiligo (AYUSHDHARA, 2025)
Vitiligo, also known as Shwitra or Kilasa in Ayurveda, is the most common pigmentation disorder. It is characterized by an imbalance of the three Doshas (Vata, Pitta and Kapha), affecting the Rakta, Mamsa and Meda Dhatus. Although Shwitra is harmless, it poses a significant cosmetic issue that can impact the emotional, psychological and social well-being of individuals. In a case involving a 14-year-old male diagnosed with vitiligo (Shwitra), the patient experienced increasing depigmented patches on the skin. The management of this condition followed Ayurvedic principles and involved a treatment protocol designed based on the patient's symptoms. The treatment starts with a combination of herbal drugs such as Mahamanjishtadi Ghanvati, Praval Pisti, Bakuchi Churna and Shuddh Swarna Gairika taken orally. Additionally, Somaraji Taila was applied locally. This protocol was effective in reversing the depigmented patches, leading to re-pigmentation. Future cases may adopt similar protocols, using different combinations of drugs based on Ayurvedic parameters, to achieve even better results.